The Role of Agricultural Extension Agents in the Marketing of 'Sang Mulyo' Banana Plantlets - Gumoyo Mumpuni Ningsih; Festy Putri Ramadhani; Wahid Muhammad Shodiq (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
This study aimed to assess the influence of agricultural extension agents on farmers’ marketing decisions concerning the Sang Mulyo banana seed variety. The research involved 21 members of the Bumi Mulyo Farmer Group in Sidomulyo Village, Dampit District, Malang Regency. Multiple linear regression analysis was conducted to examine the impact of four distinct extension roles educator, innovator, mediator, and facilitator on the implementation of marketing strategies. The findings indicate that the roles of educator and innovator had a statistically significant positive effect on marketing decisions, whereas the roles of motivator and facilitator did not exhibit a significant influence.